SUPER ENKRIPSI ALGORITMA ROUTE CIPHER DAN ALGORITMA VARIABLY MODIFIED PERMUTATION COMPOSITION (VMPC) UNTUK PENGAMAN FILE CITRA - Siagian, Fadliansyah (UNIVERSITAS STEKOM, 2024)
Securing image files is a crucial aspect in addressing information security challenges. Super encryption is an approach that combines various cryptographic algorithms to enhance data security. In this research, we implement Super Encryption by combining two algorithms, namely Route Cipher and VMPC (Variably Modified Permutation Composition). Firstly, we employ the Route Cipher to encrypt image files by rearranging the pixels in the image using a specific mapping scheme. Subsequently, we apply VMPC, a key-symmetric encryption algorithm, to encrypt the previously modified image. The use of VMPC as the second layer aims to provide additional security by incorporating efficient and secure key-symmetric encryption. The results of this research demonstrate that the combination of Route Cipher and VMPC provides strong security for image files. This method introduces a high level of complexity for attackers attempting to decrypt the image without the correct key. Moreover, this Super Encryption offers higher confidentiality and resilience against attacks on image files compared to using a single encryption algorithm.